2020
DOI: 10.1007/s00011-020-01401-6
|View full text |Cite
|
Sign up to set email alerts
|

The coagulopathy, endotheliopathy, and vasculitis of COVID-19

Abstract: Background COVID-19-associated coagulopathy (CAC) characterized by the elevated D-dimer without remarkable changes of other global coagulation markers is associated with various thrombotic complications and disease severity. The purpose of this review is to elucidate the pathophysiology of this unique coagulopathy. Methods The authors performed online search of published medical literature through PubMed using the MeSH (Medical Subject Headings) term "COVID-19," "SARS-CoV-2," "coronavirus," "coagulopathy," and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
374
0
35

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(422 citation statements)
references
References 62 publications
13
374
0
35
Order By: Relevance
“… 31 It is also reported that thrombotic microangiopathy related to direct or indirect damage by SARS-CoV-2 to the vascular endothelium can occur. 32 In our case, the punctate signal abnormalities largely resolved within 3 weeks, suggesting microthrombi as the most likely aetiology. The child was clinically normal at the 3-month follow-up.…”
Section: Discussionsupporting
confidence: 53%
“… 31 It is also reported that thrombotic microangiopathy related to direct or indirect damage by SARS-CoV-2 to the vascular endothelium can occur. 32 In our case, the punctate signal abnormalities largely resolved within 3 weeks, suggesting microthrombi as the most likely aetiology. The child was clinically normal at the 3-month follow-up.…”
Section: Discussionsupporting
confidence: 53%
“…Accordingly, the cell-based model of hemostasis and whole blood viscoelastic and platelet function tests are more appropriate to mirror the pathophysiology of COVID-19–associated coagulopathy. 3 , 4 …”
mentioning
confidence: 99%
“…IS tends to occur in those with more medical comorbidities [ 10 ], but can also occur in patients without preconditions and/or under the age of 55 [ [11] , [12] , [13] ], suggesting even healthy people are at risk. COVID-19 is thought to lead to increased thrombotic events such as IS secondary to hypercoagulability caused by systemic inflammation, viral-induced endothelial damage and cardiac dysfunction [ 8 , [14] , [15] , [16] , [17] ]. Multiple studies report that most COVID-19 related IS are cryptogenic or embolic stroke of undetermined significance (ESUS), which is a stroke subtype thought to be caused mostly by an undiagnosed cardioembolic source [ 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%